Causal association of adipokines with osteoarthritis: a Mendelian randomization study - Fan, Jiayao; Zhu, Jiahao; Sun, Lingling; Li, Yasong; Wang, Tianle; Li, Yingjun (Rheumatology (Oxford, England), 2021)
Abstract Objective This two-sample Mendelian randomization study aimed to delve into the effects of genetically predicted adipokine levels on OA. Methods Summary statistic data for OA originated from a meta-analysis of a genome-wide association study with an overall 50 508 subjects of European ancestry. Publicly available summary data from four genome-wide association studies were exploited to respectively identify instrumental variables of adiponectin, leptin, resistin, chemerin and retinol-blinding protein 4. Subsequently, Mendelian randomization analyses were conducted with inverse variance weighted (IVW), weighted median and Mendelian randomization-Egger regression. Furthermore, sensitivity analyses were then conducted to assess the robustness of our results. Results The positive causality between genetically predicted leptin level and risk of total OA was indicated by IVW [odds ratio (OR): 2.40, 95% CI: 1.13–5.09] and weighted median (OR: 2.94, 95% CI: 1.23–6.99). In subgroup analyses, evidence of potential harmful effects of higher level of adiponectin (OR: 1.28, 95% CI: 1.01–1.61 using IVW), leptin (OR: 3.44, 95% CI: 1.18–10.03 using IVW) and resistin (OR: 1.18, 95% CI: 1.03–1.36 using IVW) on risk of knee OA were acquired. However, the mentioned effects on risk of hip OA were not statistically significant. Slight evidence was identified supporting causality of chemerin and retinol-blinding protein 4 for OA. The findings of this study were verified by the results from sensitivity analysis. Conclusions An association between genetically predicted leptin level and risk of total OA was identified. Furthermore, association of genetically predicted levels of adiponectin, leptin and resistin with risk of knee OA were reported.